An MHD couple stress fluid due to a perforated sheet undergoing linear stretching with heat transfer. (February 2017) - Mahabaleshwar, U.S.; Sarris, I.E.; Hill, A.A.; Lorenzini, Giulio; Pop, Ioan
Graphical abstract: Schematic of the two-dimensional stretching sheet problem. Highlights: Governing equations are transformed to a nonlinear ordinary differential equation. The analytical solution of the stretching/shrinking sheet problem is found. Results are important to liquid-based systems involving stretchable materials. Temperatures of PHF and PST cases are qualitatively similar, but not quantitatively. PHF case is better suited for effective cooling of the linear stretching sheet. Abstract: We investigate an MHD couple stress liquid due to a perforated sheet undergoing linear stretching with radiation. The liquid is initially at rest with its activity is restricted by pulling the two sheet ends with parallel and identical forces. The consequential movement of the or else quiescent fluid is consequently generated exclusively by the stirring plate that develops a linearly varied speed with the distance from the slit. In addition to fluid flow, heat transfer with two cases of different boundary conditions from the sheet is considered, the first with prescribed surface temperature and, the second with prescribed heat flux. The arising set of non-linear coupled nonlinear partial differential equations is rehabilitated into non-linear ordinary differential equations and then exact expressions are derived for velocity and by means of a power series method with Kummer's confluent hyper-geometric functions for temperature.